2016
DOI: 10.1371/journal.pone.0151112
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Efficacy and Cardiotoxicity of Fixed-Dose Monthly Trastuzumab in HER2-Positive Breast Cancer: A Single Institutional Analysis

Abstract: ObjectiveTrastuzumab-containing treatment regimens have been shown to improve survival outcomes in HER2-positive breast cancer (BC). It is much easier to infuse a fixed one-vial dose to every patient on a regular schedule in the general clinical setting. The aims of this study were evaluating the efficacy of a 440 mg fixed-dose of trastuzumab administered on a monthly infusion schedule, and the risk factors for cardiac events.Patients and methodsWe retrospectively reviewed data from 300 HER2-positive BC patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…65,66 To decrease frequent visits for those receiving H 6 P, we offer extending the dosing interval from 3 weeks to 4 weeks, especially if receiving other treatments every 4 weeks. 67 We advise caution in the use of therapies with high risk of pulmonary toxicity, such as immunotherapy for metastatic TNBC 68 or trastuzumab deruxtecan for HER2-positive MBC. 69 For HR-positive MBC, we generally continue ET and targeted therapies that are well tolerated.…”
Section: Metastatic Breast Cancermentioning
confidence: 99%
“…65,66 To decrease frequent visits for those receiving H 6 P, we offer extending the dosing interval from 3 weeks to 4 weeks, especially if receiving other treatments every 4 weeks. 67 We advise caution in the use of therapies with high risk of pulmonary toxicity, such as immunotherapy for metastatic TNBC 68 or trastuzumab deruxtecan for HER2-positive MBC. 69 For HR-positive MBC, we generally continue ET and targeted therapies that are well tolerated.…”
Section: Metastatic Breast Cancermentioning
confidence: 99%
“…Trastuzumab has been reported to dysregulate HER2 signaling pathways and suppress autophagy by activating autophagy-inhibitory Erk/mTOR/Ulk 1 signaling cascade in cardiomyocytes and overtly resulting in the massive mitochondrial and toxic reactive oxygen species (ROS) accumulation in human cardiomyocytes [ 6 , 7 ]. As a clinical strategy of preventing the development of trastuzumab-induced cardiotoxicity, Wu et al [ 8 ] recently investigated and reported the clinical efficacy and attenuation of trastuzumab-induced cardiac dysfunction in HER2-positive breast cancer patients using fixed 440 mg dose monthly administration of trastuzumab. Unfortunately, till date, there are no approved effective therapeutic agent(s) available that could prevent the development of this unwanted/adverse effect of trastuzumab without comprising its efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, there are no prospective studies evaluating the clinical efficacy of fixed-dose intravenous regimens. One retrospective study from Taiwan 4 compared the efficacy and safety of weight-based and fixed-dose regimens. Data from 181 patients who received regular weight-based TRA every 3 weeks were compared with that from 119 patients who received monthly fixed doses of 440 mg every 4 weeks as part of adjuvant or palliative treatment.…”
mentioning
confidence: 99%